Etiological Structure Salmonellosis in Toddlers - S. Sh. Rozhnova; N. K. Akulova; O. A. Khristukhina (Эпидемиология и вакцинопрофилактика, 2015)
An analysis of official statistics and monitoring of salmonella presented multiyear incidence and etiological structure of salmonella in different age groups. It is shown that the major etiologic significance of Salmonella leading serovars in toddlers (0 - 1 years) is different from that of the older age groups (1 - 2 and 3 - 6 years), which may indicate the possible significance of domestic factors of transmission of infection in this age group.